# How do you simplify abs{-28} + abs{+3} -abs {-23} + abs{+76} - abs{+62}?

Jan 9, 2017

See full simplification process below

#### Explanation:

First, evaluate each of the terms within the absolute value functions. The absolute value function takes any negative or positive number and transforms it into its positive form:

$\left\mid - 28 \right\mid + \left\mid + 3 \right\mid - \left\mid - 23 \right\mid + \left\mid + 76 \right\mid - \left\mid + 62 \right\mid \to$

$\left(28\right) + \left(3\right) - \left(23\right) + \left(76\right) - \left(62\right) \to$

$31 - \left(23\right) + \left(76\right) - \left(62\right) \to$

$8 + \left(76\right) - \left(62\right) \to$

$84 - \left(62\right) \to$

$22$

Jan 9, 2017

The valur of this expression is $22$

#### Explanation:

To write this expression without absolute value signs you have to remember that:

## $\left\mid x \right\mid = \left\{\begin{matrix}x & x \ge 0 \\ - x & x < 0\end{matrix}\right.$

In other words if you leave the absolute value sign you change the negative number to positive, and leave positive number unchanged.

$| - 28 | + | + 3 | - | - 23 | + | + 76 | - | + 62 | =$
$= 28 + 3 - 23 + 76 - 62 = 22$